Treatment of pityriasis versicolor with topical application of essential oil of Cymbopogon citratus (DC) Stapf - therapeutic pilot study Tratamento de pitiríase versicolor com aplicação tópica do óleo essencial de Cymbopogon citratus (DC) Stapf - estudo terapêutico piloto - Egberto Santos Carmo; Fillipe de Oliveira Pereira; Neuza Maria Cavalcante; Carla Wanderley Gayoso; Edeltrudes de Oliveira Lima (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Pityriasis versicolor is a fungal infection caused by Malassezia spp. that has frequent relapses. OBJECTIVES: The main objective of this research was to perform phase I and II clinical studies, using formulations containing essential oil of Cymbopogon citratus in patients with pityriasis versicolor. METHODS: Phase I study included twenty volunteers to ascertain the safety of the formulations. In phase II, 47 volunteers randomly received essential oil formulations at 1.25 μL/mL concentration, for forty days. The shampoo should be applied three times a week and the cream twice a day. A control group in phase II, consisting of 29 volunteers, received the same formulations but with 2% ketoconazole as the active ingredient. RESULTS: No significant adverse events were observed in volunteers during Phase I. In Phase II, 30 (63.83%) volunteers using essential oil and 18 (62.07%) using ketoconazole remained until the end of the study. We observed a predominance of lesions in disseminated form, with M. sympodialis detected as the predominant agent identified in cultures. After 40 days of treatment, the rate of mycological cure was 60% (p <0.05) for the group treated with essential oil of C. citratus and over 80% (p <0.05) for the group treated with ketoconazole formulations. CONCLUSIONS: Notwithstanding the safety and antifungal effects observed in this study after application of formulations containing the essential oil of C. citratus, further studies with larger populations should be performed to confirm the actual potential of these formulations in the treatment of patients with Pityriasis versicolor. FUNDAMENTOS: Pitiríase versicolor é uma micose causada pela Malassezia spp., e que apresenta frequentes recidivas. OBJETIVOS: Este trabalho objetivou realizar estudos clínicos de fase I e II, para essa patologia, com óleo essencial de Cymbopogon citratus. MÉTODOS: Na fase I, participaram vinte voluntários para averiguar a segurança das formulações. Na fase II, 47 voluntários receberam as formulações do óleo essencial a 1,25 μL/mL, as quais deveriam ser utilizadas por quarenta dias, sendo o xampu três vezes por semana e o creme duas vezes ao dia. Um grupo controle na fase II, constituído por 29 voluntários recebeu as mesmas formulações, com cetoconazol a 2%. RESULTADOS: Verificada a segurança das formulações com a finalização da fase I, onde nenhuma reação adversa significativa foi observada nos indivíduos sadios, conduziu-se a fase II. Nesta segunda fase, 30 (63,83%) voluntários utilizando óleo essencial e 18 (62,07%) cetoconazol permaneceram até o final do estudo. Observaram-se nos pacientes com pitiríase versicolor predomínio de lesões na forma disseminada e M. sympodialis foi o agente predominante identificado em cultura. Após 40 dias de tratamento, obteve-se um percentual de cura micológica de 60% (p < 0,05) para o grupo tratado com óleo essencial de C. citratus e superior a 80% (p < 0,05) para o grupo tratado com cetoconazol. CONCLUSÕES: Apesar da segurança e efeito antifúngico observados após aplicação das formulações contendo óleo essencial de C. citratus, outros estudos com maior número de portadores de pitiríase versicolor precisam ser realizados para confirmar o real potencial destas formulações.